Analisis Faktor-faktor yang Memengaruhi Minat Masyarakat Terhadap Urban Farming (Kasus pada Kelurahan Sungai Jawi Dalam Pontianak Kota) - Putera, Geger Nusantara; Yurisinthae, Erlinda; Maswadi, Maswadi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The high rate of conversion of rice fields and the concomitant population is increasing and decreasing food availability at the same time, it also gives an impact of decreasing food production which can pose a threat to the population's food security. The increasing population density in Pontianak causes limited land. Due to limited land, people in Pontianak City have to find ways to grow crops in a narrow environment and with minimal land. urban farming is an agricultural activity carried out in an urban environment. This activity includes a variety of activities, from growing vegetables, fruit, flowers, to raising animals. This study was conducted in the Sungai Jawi Dalam sub-district, with the location being determined purposively. Descriptive quantitative is used by the writer and used primary data obtained directly from the chosen research place. The sampling technique applied is purposive sampling, consist of of 32 individuals as total sample. The writer apply method is Partial Least Square (PLS) to analyze. The results of this research show that the Business Opportunity variable has no effect on urban farming Interest, while the Land Use variable has an effect on urban farming Interest with a p value shows 0.008 or higher than 0.005 and 0.479 for an original sample value is indicating a positive relationship direction and is able to explain urban farming Interest. 47.9%.